2017
DOI: 10.1177/1553350616687435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity on Perioperative Outcomes After Robotic-Assisted Pulmonary Lobectomy

Abstract: Patients with obesity do not have increased risk of intraoperative or postoperative complications, except for pneumonia, compared with "normal weight" and "overweight" patients. Robotic-assisted pulmonary lobectomy is safe and effective for patients with high BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
(53 reference statements)
3
6
0
Order By: Relevance
“…In particular, our findings are in contrast with St Julien et al that investigated the database of the society of thoracic surgeons and observed an increased operating time by 7.2 min for every 10-unit increase in BMI [ 29 ]. On the other hand, our results were in line with a recent study on RATS lobectomy that demonstrated equivalence in surgical time between obese and non-obese patients [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In particular, our findings are in contrast with St Julien et al that investigated the database of the society of thoracic surgeons and observed an increased operating time by 7.2 min for every 10-unit increase in BMI [ 29 ]. On the other hand, our results were in line with a recent study on RATS lobectomy that demonstrated equivalence in surgical time between obese and non-obese patients [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…For all these reasons, it could be intuitive that patients with elevated BMI developed more frequently post-operative complications. Nevertheless, the current literature presents contradictory results on this topic, and the “obesity paradox,” namely the protective effect of obesity on complication incidence, has been observed also in the thoracic surgery cohort analysis [ 24 28 ]. On the other hand, several studies presented a higher incidence of complications (notably pulmonary ones) in obese patients submitted to thoracic surgery [ 12 , 21 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The obese patients have a higher risk for pneumonia, atelectasis, and other postoperative complications [ 33 , 34 ]. HFNC with high adherence rate, comfortable experience, and lower costs has emerged as a new oxygen supportive treatment, but the efficacy of HFNC for obese patients during the perioperative period is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is considerable disagreement within the literature about the effect of obesity on pneumonia following lung cancer surgery, as some studies also found a protective effect of obesity or higher BMI, 39 , 40 , 41 whereas other studies have found obesity to be a risk factor. 4 , 42 , 43 …”
Section: Commentmentioning
confidence: 99%